Revenues and expenditures of local budgets in conditions of decentralization of power: legal aspect. - Vdovichen, Vitalii (Journal of law and political science, 2023)
The issue of the efficiency of forming local budgets occupies a central place in the process of analyzing the social-economic development of territories. The purpose of the academic paper is to highlight the theoretical features of the legal component in the process of forming local budgets in the conditions of decentralization of power, as well as to clarify the features of the practical aspects of the issue outlined. In the course of the research, analytical and bibliographic methods were used to study the scientific literature on the formation of local budgets. The research authors also conducted a questionnaire in online mode to practically clarify the most important issues related to managing the budget process under the condition of decentralization of power. Based on the research results, the primary and most significant theoretical aspects of the issue of forming the revenue and expenditure part of local budgets in the process of decentralization of power were established. At the same time, the standpoints of scientists and heads of departments of local self-government bodies regarding key aspects of this issue were studied.
Keywords: Territorial Development; Legislative Consolidation of Local Self-Government Functions; Decentralization of Budget Funds Management; Financial Management of Local Self-Government